DAMPAK PEMBINAAN DISIPLIN KERJA APARATUR SIPIL NEGARA DI DINAS BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DI KOTA TOMOHON - BUMULO, HIZKIA EDICHANDRA JOHN; POSUMAH, JOHNNY HANNY; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2020)
The State Civil Apparatus (SCA) as a government apparatus works to serve the interests of the communityand works according to state duties and is paid according to what has been regulated in the law. GovernmentRegulation Number 53 of 2010 concerning the discipline of Civil Servants or State Civil Servants is used asa reference for regulating obligations and prohibitions for civil servants, types of disciplinary punishment,as well as officials authorized to provide disciplinary sentences. The purpose of this study is to determinethe impact of coaching on the work discipline of the State Civil Apparatus in the Civil Service and HumanResources Development Agency of Tomohon City, as well as to find out what obstacles are faced in theimplementation of guidance and discipline improvement of the State Civil Apparatus. This research methodis a qualitative research method carried out to the State Civil Apparatus in the Civil Service and HumanResources Development Agency of Tomohon City, and the State Civil Apparatus in the City of Tomohon.The data sources were interviews and documents. The data validity was done by triangulating the data. Theresult of this research is that in an effort to improve the discipline of the State Civil Apparatus (ASN) ofTomohon City, coaching efforts are made, namely preventive coaching and corrective coaching. Preventivecoaching is carried out to all State Civil Apparatus in the city of Tomohon by disseminating GovernmentRegulation Number 53 of 2010 concerning Civil Servant discipline, and in the form of submitting to allHeads of Regional Apparatus Work Regulations, regarding working hours regulations, official uniformsfor the implementation of the apple and attendance presence. Corrective disciplinary fostering of the StateCivil Apparatus shall be carried out on officials who violate discipline by imposing disciplinary penalties.Disciplinary penalties are categorized into three, namely, mild disciplinary punishment, moderatedisciplinary punishment, and severe disciplinary punishment. The development of preventive State CivilApparatus work discipline has generally been carried out well, but the results have not been optimal, whilethe corrective discipline guidance carried out has a positive impact on the officials who are sentenced,because afterwards the performance of these official gets better, The things that become obstacles in theprocess of disciplinary development are humanitarianism, pity, and awkwardness when conductingdisciplinary guidance.Keywords: State Civil Apparatus, Coaching, fostering, Work.